2016
DOI: 10.1021/jacs.5b10445
|View full text |Cite
|
Sign up to set email alerts
|

Side-Chain-Induced Rigid Backbone Organization of Polymer Semiconductors through Semifluoroalkyl Side Chains

Abstract: While high-mobility p-type conjugated polymers have been widely reported, high-mobility n-type conjugated polymers are still rare. In the present work, we designed semifluorinated alkyl side chains and introduced them into naphthalene diimide-based polymers (PNDIF-T2 and PNDIF-TVT). We found that the strong self-organization of these side chains induced a high degree of order in the attached polymer backbones by forming a superstructure composed of "backbone crystals" and "side-chain crystals". This phenomenon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
219
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(224 citation statements)
references
References 51 publications
(83 reference statements)
5
219
0
Order By: Relevance
“…Kang et al reported high‐performance n‐type polymers by incorporating semifluorinated alkyl side chains in NDI‐based polymers ( P35 and P36 ) . Owing to the strong self‐organization between fluorinated side chains, both polymers formed highly ordered crystalline structures and exhibited a μ e value of about 4 cm 2 V −1 s −1 .…”
Section: Molecular Design Strategies For High‐performance D–a‐conjugamentioning
confidence: 99%
“…Kang et al reported high‐performance n‐type polymers by incorporating semifluorinated alkyl side chains in NDI‐based polymers ( P35 and P36 ) . Owing to the strong self‐organization between fluorinated side chains, both polymers formed highly ordered crystalline structures and exhibited a μ e value of about 4 cm 2 V −1 s −1 .…”
Section: Molecular Design Strategies For High‐performance D–a‐conjugamentioning
confidence: 99%
“…These include chemical and thermal stability, hydrophobicity and a self‐assembly ability . For this reason, fluoroalkyl chains are attached to conjugated polymers to tune their solid state structures and improve their semiconducting performances . The studies reveal that the unique fluorophobic interactions due to the fluoroalkyl chains can promote the polymer chains to form more orderly assembly structures and thus boost their charge transporting properties.…”
Section: Side Chains With Heteroatoms and Functional Groupsmentioning
confidence: 99%
“…Therefore, modification of side alkyl chains has gradually became an efficient approach to boost the charge mobilities of semiconducting conjugated polymers . Furthermore, heteroatoms and functional groups are incorporated into the side chains of conjugated polymers, not only for improving the semiconducting property but also for endowing the polymers with sensing and responsive functionalities . Increasing numbers of results demonstrate that i) the semiconducting performances of conjugated polymers can be improved by varying the side chains without changing the conjugated backbones, ii) highly selective and sensitive FET‐based sensors can be achieved by incorporating functional groups in the side chains of conjugated polymers, and iii) stimuli‐responsive semiconductors can be generated by linking photoresponsive groups in the side chains of conjugated polymers.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it was reported that charge mobilities of isoindigo/DPP‐based conjugated polymers were enhanced by moving the branching points of branching alkyl chains away from the conjugated backbone 2, 28. Increased charge mobilities were also reported for conjugated polymers where pure alkyl side chains were replaced with siloxane‐terminated alkyl, fluoroalkyl, or oligo(ethylene glycol) chains 29, 30, 31, 32, 33, 34, 35, 36. Taking advantage of the formation of hydrogen bonding between urea groups, we introduced urea groups in the side alky chains of DPP‐quaterthiophene conjugated polymers to improve interchain packing order and thin‐film morphology, resulting in large enhancement of hole mobilities 33…”
Section: Introductionmentioning
confidence: 99%